Beyond Competence: Rethinking Education for Holistic Well-Being and Happiness - Ibnu Fitrianto (Yayasan Azhar Amanaa Yogyakarta, 2025)
Traditional education systems often prioritize academic achievement and competency development while overlooking students' emotional well-being. However, increasing cases of stress, anxiety, and burnout among students highlight the need for a more balanced educational approach. This study explores the concept of happiness-based education, examining its impact on student motivation, engagement, and overall well-being. Using a qualitative approach with case studies and phenomenological analysis, the research investigates educational institutions that have successfully implemented happiness-centered learning models. Data were collected through in-depth interviews, classroom observations, and document analysis related to policies on student well-being. The findings indicate that integrating mindfulness, social-emotional learning, and value-based curricula significantly enhances both academic performance and students' psychological development. Despite its benefits, challenges such as curriculum adjustments, teacher training, and policy support remain obstacles to widespread implementation. This study concludes that collaborative efforts between educators, parents, and policymakers are essential for sustaining happiness-based education and ensuring a holistic learning experience. Future research should focus on cross-cultural comparisons and long-term outcomes of this educational mode